Structure and strength of the distal radius in female patients with rheumatoid arthritis: A case‐control study. (18th March 2013) - Zhu, Tracy Y; Griffith, James F; Qin, Ling; Hung, Vivian WY; Fong, Tsz‐Ning; Au, Sze‐Ki; Tang, Xiao Lin; Kwok, Anthony W; Leung, Ping‐Chung; Li, Edmund K; Tam, Lai‐Shan
Abstract The purpose of this work was to investigate the volumetric bone mineral density (vBMD), bone microstructure, and mechanical indices of the distal radius in female patients with rheumatoid arthritis (RA). We report a cross‐sectional study of 66 middle‐aged female RA patients and 66 age‐matched healthy females. Areal BMD (aBMD) of the hip, lumbar spine, and distal radius was measured by dual‐energy X‐ray absorptiometry (DXA). High‐resolution peripheral quantitative computed tomography (HR‐pQCT) was performed at the distal radius, yielding vBMD, bone microstructure, and mechanical indices. Cortical and trabecular vBMD were 3.5% and 10.7% lower, respectively, in RA patients than controls, despite comparable aBMD. Trabecular microstructural indices were –5.7% to –23.1% inferior, respectively, in RA patients compared to controls, with significant differences in trabecular bone volume fraction, separation, inhomogeneity, and structural model index. Cortical porosity volume and percentage were 128% and 93% higher, respectively, in RA patients, with stress being distributed more unevenly. Fourteen RA patients had exaggerated periosteal bone apposition primarily affecting the ulnovolar aspect of the distal radius. These particular patients were more likely to have chronic and severe disease and coexisting wrist deformity. The majority of the differences in density and microstructure between RA patients and controls did not depend on menstrual status. Recent exposure to glucocorticoids did not significantly affect bone density and microstructure. HR‐pQCT provides new insight into inflammation‐associated bone fragility in RA. It detects differences in vBMD, bone microstructure, and mechanical indices that are not captured by DXA. At the distal radius, deterioration in density and microstructure in RA patients involved both cortical and trabecular compartments. Excessive bone resorption appears to affect cortical more than trabecular bone at distal radius, particularly manifested as increased cortical porosity. Ulnovolar periosteal apposition of the distal radius is a feature of chronic, severe RA with wrist deformity. © 2013 American Society for Bone and Mineral Research.